ANALISIS KEPUTUSAN BERINVESTASI DI UMKM MELALUI SECURITIES CROWDFUNDING: PENDEKATAN THEORY OF PLANNED BEHAVIOR - Muhammad Adil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Since its introduction in 2018, Securities Crowdfunding (SCF) has experienced annual growth in terms of organizers, issuers, investors, and the amount of funds raised. However, starting in 2021, there has been a decrease in the growth rate, indicating a slowing market in crowdfunding investments. This study aims to analyze the influence of Attitude, Subjective Norm, and Financial Efficacy on Intention and Investment Decision in SCF by collecting data from 100 respondents who have already invested or plan to invest in SMEs through SCF, gathered through a Google Forms survey. The measurement of these variables will be analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) research method. The results of the study indicate that Attitude and Subjective Norm have a positive correlation with investment intention, while investment intention has a positive correlation with investment decisions in SMEs through SCF. However, Financial Efficacy has a negative correlation with investment intention in SMEs through SCF. The findings of this study indicate that intention is a factor influencing investment decisions in SMEs through SCF, as indicated by the positive correlation. Attitude and Subjective Norm have a positive correlation that forms Intention. Meanwhile, Financial Efficacy has a negative correlation with Intention, indicating that Financial Efficacy does not provide strong evidence in shaping the intention to invest in SMEs through SCF. The implications of these findings are to provide understanding to investors and SCF platforms regarding the factors influencing investment decisions in SMEs through SCF. This research can also serve as a basis for the development of literature on SCF and provide recommendations to the government and SCF platforms to enhance investor participation in investing in SMEs through SCF.